Methylseleninic Acid Sensitizes Ovarian Cancer Cells to T-Cell Mediated Killing by Decreasing PDL1 and VEGF Levels - Nair, Deepika; Rådestad, Emelie; Khalkar, Prajakta; Diaz-Argelich, Nuria; Schröder, Axel; Klynning, Charlotte; Ungerstedt, Johanna; Uhlin, Michael; Fernandes, Aristi P. (Frontiers in Oncology, 2018)
Redox active selenium (Se) compounds at sub toxic doses act as pro-oxidants with cytotoxic effects on tumor cells and are promising future chemotherapeutic agents. However, little is known about how Se compounds affect immune cells in the tumor microenvironment. We demonstrate that the inorganic Se compound selenite and the organic methylseleninic acid (MSA) do not, despite their pro-oxidant function, influence the viability of immune cells, at doses that gives cytotoxic effects in ovarian cancer cell lines. Treatment of the ovarian cancer cell line A2780 with selenite and MSA increases NK cell mediated lysis, and enhances the cytolytic activity of T cells. Increased T cell function was observed after incubation of T cells in preconditioned media from tumor cells treated with MSA, an effect that was coupled to decreased levels of PDL1, HIF-1-alpha, and VEGF. In conclusion, redox active selenium compounds do not kill or inactivate immune cells at doses required for anti-cancer treatment, and we demonstrate that MSA enhances T cell-mediated tumor cell killing via PDL1 and VEGF inhibition.